Greenhouses of Hope: Congregations Growing Young Leaders Who Will Change the World - Baker, Dorie Grinenko (Rowman & Littlefield Publishers, 2010)
Do you know a church where young people regularly shape the liturgy with words that speak their truth in ways that also inspire their elders? Do you hear about congregations that reach out in quirky new ways to their ailing neighborhoods, instead of locking doors and shipping out to a suburb? Do you find churches creating hospitable space that invites the live wriggling questions and doubts of young people in unhurried, unworried ways? Do you see congregations where young people's gifts are not stored in the basement or bracketed into 'contemporary' worship services but are brought forth and celebrated? The authors who collaborated on this book launched a quest for such vibrant, life-giving, greening congregations and observed the diverse practices that grow there. They named these churches 'Greenhouses of Hope.' A Greenhouse of Hope is a Christian congregation freeing itself to experiment with both newly imagined and time-honored ways of following the path of Jesus. Its members respond to God's love through practices that genuinely embrace the gifts of youth and young adults. Out of these greenhouses emerge young leaders who want to change the world. In Greenhouses of Hope, Dori Baker and six contributors tell the stories of these remarkable congregations, helping others think about how they can create space for the dreams of young people to be grafted into God's dreams for the world